2019
DOI: 10.5334/aogh.2535
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollution in Kazakhstan and Its Health Risk Assessment

Abstract: Background:Air pollution in Kazakhstan is caused by many factors and poses serious threats to public health. Ambient air in the cities of Kazakhstan is polluted due to mining and processing of mineral resources, oil and gas production, gasoline and diesel fuel motor vehicles, industrial enterprises.Objective:The study aim is to assess the air pollution degree in most significant settlements of Kazakhstan and define risk levels for the population health. Ambient air monitoring was conducted in 26 cities. Air po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 16 publications
0
23
1
1
Order By: Relevance
“…Due to the lack of large population-based vitamin D studies in Kazakhstan, it is unclear if high incidence rates of leukemia in the Karaganda region observed during 2003-2013 [18] are related to the prevalence of vitamin D deficiency in Central Kazakhstan [17]. Leukemia incidence in this area may be influenced by multiple important factors, including its proximity to the former Semipalatinsk nuclear test site and high levels of toxic air pollutants [45]. Although our present pilot study is observational and involves small numbers of participants, it provides initial findings that warrant a larger and more detailed investigation into the possible contribution of vitamin D deficiency to high incidence of leukemia in Central Kazakhstan and other regions of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the lack of large population-based vitamin D studies in Kazakhstan, it is unclear if high incidence rates of leukemia in the Karaganda region observed during 2003-2013 [18] are related to the prevalence of vitamin D deficiency in Central Kazakhstan [17]. Leukemia incidence in this area may be influenced by multiple important factors, including its proximity to the former Semipalatinsk nuclear test site and high levels of toxic air pollutants [45]. Although our present pilot study is observational and involves small numbers of participants, it provides initial findings that warrant a larger and more detailed investigation into the possible contribution of vitamin D deficiency to high incidence of leukemia in Central Kazakhstan and other regions of the country.…”
Section: Discussionmentioning
confidence: 99%
“…Older people have a higher risk of atrial fibrillation, dislipidemia, or coronary heart disease, which are associated with increased stroke mortality. The results of environmental studies show increased air pollution due to heavy metal exposure, coal mines, industrial enterprises, and power production in the abovementioned regions except for Kostanay 24 , which could explain the increase in the incidence of stroke in these regions. Studies have shown that air pollution and traffic noise can be important environmental risk factors for stroke in urban societies 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Currently, in the Republic of Kazakhstan in dumps, according to reports of independent assessments [1,2], more than 400 million tons of ash and slag waste from thermal power plants and metallurgical waste have been accumulated, which is an aggravation of the environmental situation in industrial regions and requires the development of technical solutions to improve it [3].…”
Section: Introductionmentioning
confidence: 99%
“…A promising raw material for the production of building products is ash and slag waste from thermal power plants and waste from the metallurgical industry [5,6]. In addition, today the scaling of the technology for the production of heavy concrete using ash and slag waste from thermal power plants and waste from metallurgy of the Republic of Kazakhstan is widely used [1,7].…”
Section: Introductionmentioning
confidence: 99%